2008
DOI: 10.4103/0255-0857.43556
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin breakpoints in enteric fever: Time to revise our susceptibility criteria

Abstract: We read with interest the article entitled "Ciproß oxacin breakpoints in enteric fever-time to revise our susceptibility criteria" by Rodrigues et al, [1] published in Jan-Mar 2008 issue of the Indian Journal of Medical Microbiology. The article is thought provoking but certain critical aspects have been overlooked, which if mentioned would be enriching for the various investigators and decision makers in this crucial area.Firstly, this study only mentions the number of nalidixic acid resistant strains isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Ciprofloxacin brings about concentration dependent killing and is 30% protein bound. Keeping the pharmacokinetic and pharmacodynamic properties for Gram negative bacteria in mind (AUC/MIC>125), a higher dose of 750mg twice daily has been successfully used in treating enteric fever [6,16]. This holds true only if the isolate has an MIC <0.176 μg/ml as the AUC at this dose would be 22.…”
Section: Discussionmentioning
confidence: 99%
“…Ciprofloxacin brings about concentration dependent killing and is 30% protein bound. Keeping the pharmacokinetic and pharmacodynamic properties for Gram negative bacteria in mind (AUC/MIC>125), a higher dose of 750mg twice daily has been successfully used in treating enteric fever [6,16]. This holds true only if the isolate has an MIC <0.176 μg/ml as the AUC at this dose would be 22.…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly because clinical staging may not be accurate to show the level of patient immune status. Studies have reported that the host immune status is one of the important determinants to influence Cryptosporidium [16,19,23,27] and S. stercoralis infection [16]. Patients with CD4 T-cell count less than 200 cells/μl of blood are in excess risk of having these infections [16].…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 12 Concurrent infection with multiple serotypes of dengue was also seen. 35 , 36 Thus, it is evident that now in India there is a definite increase in the frequency and number of outbreaks along with co-circulation of all four serotypes, hinting toward hyperendemicity of dengue in India.…”
Section: Changing Epidemiology In Indiamentioning
confidence: 99%